Experimental Research on the Transverse Effective Bending Rigidity of Shield Tunnels. (4th November 2019) - Zheng, Gang; Lei, Yawei; Cui, Tao; Cheng, Xuesong; Diao, Yu; Zhang, Tianqi; Sun, Jibin
Abstract : The uniform rigidity ring model is commonly used to design the segmented structures of shield tunnels. However, model tests have been primarily used to study the transverse effective rigidity ratio η with a concentrated force, which is notably different from realistic loading patterns. To obtain more reasonable η values, in this study, tests were performed with a concentrated load on an experimental bench and with a realistic loading pattern in sandy soil in a rigid steel tank. Three types of segmental ring models were designed and tested: straight-jointed, stagger-jointed, and uniform rings. The test results indicated that the η values of the stagger-jointed assembly mode were clearly larger than those of the straight-jointed assembly mode under both loading patterns. η increased as the load increased under the realistic loading conditions, whereas η decreased as the load increased under the concentrated load. More importantly, the η values derived from the realistic load tests were considerably larger than those derived from the concentrated load tests for both assembly modes (i.e., 0.423–0.672 and 0.587–0.761 for the straight-jointed and stagger-jointed assembly modes, respectively), and the former should be recommended for practical engineering applications. Furthermore, formulas relating η to the ratio of the cover depth to the tunnel diameter were proposed for sandy soil.